Application of International Financial Reporting Standards (IFRS) and their Impact on the Quality of Financial Reporting: An exploratory study on a group of companies in Sulaymaniyah Governorate / Iraq - Alsalem, Munadhil Abdljabar; Omar, Guldoz Mohammed Dler (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
The research is a step towards opening up to the implementation of international standards which are currently an area of concern for many countries in the world and international companies to advance financial and accounting work and improve related procedures. The study focuses on the implementation of the International Financial Reporting Standards (IFRS) and its impact on improving the quality of financial reporting (relevance and reliability) in companies operating in the Sulaymani Governorate. The research aims، in particular، to clarify the impact of the implementation of the International Financial Reporting Standards (IFRS) on improving the quality of financial reports on the one hand and، on the other hand، to encourage companies to adopt International Financial Reporting Standards (IFRS) when preparing and presenting financial reports and statements. The research was based on the questionnaire form as a field study tool، and the study was applied to a sample of companies operating in the Sulaymaniyah governorate that numbered (17) companies. Out of the (158) forms that were distributed to the sampled individuals، (144) forms were returned with a percentage (94%) of the returned forms being valid for analysis.The results of the study show that there is a positive statistically significant relationship between the implementation of the International Financial Reporting Standards (IFRS) and its impact on the quality of financial reports. The working financial environment of the Suliamani Governorate has shown that it supports and enhances the implementation of the International Financial Reporting Standards (IFRS). When these standards provide requirements for the relevance and reliability of the information content of financial reports in line with the needs of users. The implementation of international financial reporting standards has a positive impact on the relevance and reliability property and increases the accuracy of the information contained in the company's financial reports.